ANALISIS PEMOTONGAN PEMUNGUTAN PAJAK PENGHASILAN (PPh) SEBAGAI PEMENUHAN KEWAJIBAN WAJIB PAJAK PT BADAK NGL BONTANG - JUNE, CINDY GETAH TRISNA (Jurnal Mahasiswa Perpajakan, 2015)
The oil and gas sectorâ€™s of tax revenue is one of more dominant sector in rather than other taxes. PT Badak NGL is a business entity engaged in the field of oil and gas by applying the process Witholding Tax for a partner company. This research is a descriptive research with a qualitative approach. Business processes are carried out by PT Badak NGL include business Â processes with shareholders, the Company partners and buyers of processed oil are China, Japan and Taiwan. Delayed that often occur in the payment of taxes due to partners who are late in submitting invoices to PT Badak NGL Bontang. PT Badak NGL Bontang should be more careful about budgeting so that no gap between the taxes paid by fees charged Keywords: Oil and gas sector, WitholdingTax